Ethical and clinical implications for the field of marriage and family therapy regarding LGBTQI therapeutic approaches - Lugo, Cheryl A. (Kansas State University, 2010)
There are three different approaches for the treatment of lesbian, gay, bisexual, transgender, questioning, and intersex (LGBTQI) sexual orientations: reparative therapies, gay-affirmative therapies, and person-centered approach. These therapeutic approaches will be discussed individually and Kitchener’s Model of Ethical Decision Making or Moral Justification will be applied to each of them with the purpose of identifying which is the most ethical. The American Association for Marriage and Family Therapy (AAMFT) scholars have not created guidelines for working with LGBTQI or made a clear stance on what they believe would be the best approach to take, therefore, clinical and ethical implications and recommendations for the field of marriage and family therapy will be discussed.
Keywords: LGBTQI; Person-centered therapy; Gay-affirmative therapy; Reparative therapy; Conversion therapy; Aversion therapy; Psychology, General (0621)